Pengaruh Penggunaan Pupuk Kandang Dan Sistem Irigasi Alur Terhadap Ketersediaan Air Tanah Dan Pertumbuhan Cabai Merah (Capsicum Annuum L.) - Nofianti Zebua; Natalia Kristiani Lase (Jurnal Ilmu Pertanian dan Perikanan, 2026)
This study aims to determine the effect of using manure and furrow irrigation systems on soil water availability and the growth of red chili plants (Capsicum annuum L.). Agricultural land in Indonesia faces many challenges, including declining soil quality and water scarcity, which affect crop productivity. Therefore, it is important to explore solutions based on sustainable agriculture, such as the use of organic fertilizers and efficient irrigation techniques. The research was conducted using an experimental approach in agricultural fields with a quantitative method. The results showed that the application of manure and furrow irrigation significantly increased soil moisture and plant growth compared to the control treatment. These findings are consistent with several previous studies conducted by Sitorus and Tyasmoro (2019), Dewi et al. (2020), and Arifin (2021).